Baloney, Henry P. - Scieszka, Jon; Smith, Lane (New York: Viking, 2001)
A transmission received from outer space in a combination of different Earth languages tells of an alien schoolboy's fantastic excuse for being late to school again.
Keywords: Life on other planets -- Fiction; Schools -- Fiction